1985
DOI: 10.1093/cvr/19.6.326
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic damage to human saphenous vein during preparation for coronary artery bypass grafting

Abstract: Segments of saphenous vein from patients undergoing coronary artery by-pass graft surgery were frozen in liquid nitrogen immediately on dissection (control), after stripping of the adventitia and side branch ligation (manipulation), after distention with blood (distention), or at completion of the last proximal anastomosis (prepared vein). Vein was stored during the operation in patient's heparinised arterial blood at room temperature. Frozen vein was extracted with perchloric acid. ATP, ADP, and AMP, adenosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(18 citation statements)
references
References 0 publications
0
17
0
1
Order By: Relevance
“…Routine anaesthetic and surgical procedures were done. The saphenous vein was removed through an incision over the vein using conventional open technique (Angelini et al, 1985). All veins appeared without any macroscopic pathology.…”
Section: Preparation Of the Saphenous Veinmentioning
confidence: 99%
See 2 more Smart Citations
“…Routine anaesthetic and surgical procedures were done. The saphenous vein was removed through an incision over the vein using conventional open technique (Angelini et al, 1985). All veins appeared without any macroscopic pathology.…”
Section: Preparation Of the Saphenous Veinmentioning
confidence: 99%
“…Previous studies have demonstrated that uncontrolled manual distension of the saphenous vein structurally and functionally damage the endothelium (Angelini et al, 1987a, b;Chello et al, 2003;Johnson et al, 2001;Mills and Everson, 1995;Svendsen et al, 1986;Thatte and Khuri, 2001), muscle (Angelini et al, 1985(Angelini et al, , 1987aCornelissen et al, 2004;George et al, 1997;O'Brien et al, 1998), and interstitium (Kennedy et al, 1989a, b). In the present study, the wall thickness and wall area were largest in the saphenous vein with uncontrolled manual distension.…”
Section: Implication Of the Present Study For Cabgmentioning
confidence: 99%
See 1 more Smart Citation
“…Using epifluorescence multiphoton imaging techniques, we have previously shown that the pH, temperature, SV distention, and composition of storage solution can affect the endothelial viability and function [4,12-15]. Similarly, surgical manipulation can also damage the endothelium of SV grafts, increasing the risk of vasospasm, thrombogenesis, occlusive intimal hyperplasia, and stenosis [4,5,10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…12, 3136 The impact of unregulated distension on the endothelial layer is more pronounced. Peak distension pressure is proportional to endothelial loss and dysfunction in human SV.…”
Section: Discussionmentioning
confidence: 99%